Oracle 10g RAC grid, services & clustering - Vallath, Murali (Amsterdam ; Boston : Elsevier Digital Press, 2006)
Grid architecture is Oracles strategy for high-end computing and RAC is the stepping stone into this arena. This book focuses on current technology including all valid RAC features up through Oracle Database 10g Release 2, with a primary focus on deploying it in a high-end grid environment. The book discusses this technology at length which users will find beneficial when researching, implementing or monitoring a RAC environment. The author covers workshop implementation of services and the distribution of workload across instances, with threshold definitions and the new load balancing algorithms. In addition it includes detailed discussions on ASM that complements the implementation of RAC in Oracle Grid strategy. The book also includes discussions on new Oracle Clusterware, its components and its integration with RAC. Oracle 10g RAC focuses on RAC-specific topics including ASM, operating system configuration, installation and configuration of RAC and much more. Coverage includes network configuration for high availability, FAN, TAF, ONS, implementation of maximum availability architecture (MAA), EM Grid Control, AWR, ADDM and other performance-related tools. The author includes several scripts for performance tuning and implementation that the reader can use to configure a RAC environment either on a 2, 4, 8, 60 or 99 node configuration. * Focuses on implementing, testing and tuning features of Real Application Clusters (RAC) database version 10g Release 2 * Provides extensive coverage of usage, day-to-day functions and operations * Includes tips and techniques such as script samples to illustrate various features of RAC * A jumpstart into all the key features of 10g R2 RAC.
GRID, RAC Architecture, Storage Management, Installation and Configuration, Services and Distributed Workload Management, Load Balancing and Failover, Cluster Administration Quick Reference, Backup and Recovery, Performance Tuning, MAA and more, Best Practices, Appendices.
Includes index.
"Data management"--Cover.
"Includes RAC best practices chapter by Kirk McGowan, Oracle Corporation"--Cover.
Keywords: Oracle (Computer file); Relational databases; Parallel processing (Electronic computers); Electronic data processing -- Distributed processing; Beowulf clusters (Computer systems); Electronic books